THE ROLE OF THE FAMILY IN SUPPORTING THE CURE PROCESS OF PULMONARY TB PATIENTS AT THE PAMATANG RAYA HEALTH CENTER SIMALUNGUN DISTRICT - Muharti Sanjaya; Dilla Sastia Mara (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
This study entitled "The Role of the Family in Supporting the Healing Process of Pulmonary TB at the Pamatang Raya Health Center, Simalungun Regency in 2015 to June 2016." Penode June 2016 using a research design that was carried out was descriptive meaning to get an overview or description The sampling technique used in the study was purposive sampling, namely the method of determining the sample was carried out with consideration, characteristics and characteristics. This sample was taken from families of patients with bacterial pulmonary TB. positive (BTA+) who came for control to the Puskesmas according to the schedule determined to come back to take the medicine.The number of positive pulmonary TB patients (50 people with AFB, of these 31 people with positive pulmonary TB (BTA +) accompanied by families who were used as research samples at the Pamatang Raya Health Center, Simalungun Regency from 2015 to June 2016 period. The results of this study indicate that identification of the role of the family for the treatment of pulmonary TB at the Pamatang Raya Health Center in 2015 to the period June 2016, there were 31 respondents with the most characteristics being 22-29 years old (32.3%) as many as 10 people with last high school education as many as 11 respondents (35.5%) Release the results the research found that the most family role was enough with the number of respondents 16 people (51.6%) The results of this study found that the majority of families have a family role that is not good or sufficient in supporting the treatment process for pulmonary TB patients, so it is hoped that nurses can further enhance the role of the family with health education so that the role of the family in the treatment of pulmonary TB patients becomes very good.